Health education: the importance of the correct disposal of expired or unused household medications (Research, Society and Development, 2022)
Medicines are pointed out as emerging micropollutants, their inadequate disposal in inappropriate places, can cause negative effects to human health and the environment. The pharmacist, as a health educator, should guide the rational use and proper disposal of expired or unused medicines. Health education promotes autonomy, responsibility, and greater participation of individuals in health care. With the goals of educating the community about the importance of proper disposal, analyzing how medicines are being disposed of at home, reflecting on the environmental and health risks of improper disposal, and possible solutions, the Pharmacy School UFPR promoted an educational campaign on the conscious disposal of medicines. During the campaign, a questionnaire was applied to check the perception and knowledge about the theme, orientations and clarifications, and interactive posters were displayed. A total of 515 people were interviewed, of which 48.13% disposed of their medication incorrectly, 59.51% stated that the medication expired due to treatment leftovers, and 65.82% of the participants stated that they had never seen campaigns about medication disposal and, after the approach, 91.63% of the interviewees reported that the information passed on was useful. The inadequate disposal of expired or unused medicines is a public health problem. Thus, the adoption of measures for the development of educational campaigns, correct use and disposal, responsible self-medication, the practice of fractionated sales, and the implementation of integrated reserve logistics is necessary to solve this problem.